2022
DOI: 10.3390/vetsci9100575
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Brucella Seroprevalence in Wild Boar Population in Serbia

Abstract: Brucellosis is one of the most important bacterial zoonotic diseases worldwide, characterized in domestic animals by long-term reproductive disorders. As known, wild boars (Sus scrofa) are natural hosts for Brucella suis biovar 2, in which the infection passes in inapparent form, increasing the pathogen transmission risk to domestic pigs, other domestic animals and humans. So far, no studies regarding brucellosis in wild boars in Serbia have been published. During the hunting season 2020/2021, 480 sera of wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…seroprevalence varies widely in different European countries; B. suis is mainly present in wild boars and in European brown hares (Lepus europaeus) [60][61][62][63][64]. A global comprehensive literature review and meta-analysis of Brucella in pigs from 2000 to 2020 reported that the overall prevalence of brucellosis in wild boars between 2006 and 2010 was 22.3%, while after 2010, the prevalence gradually decreased after the WOAH proposed control safety standards for animal production [65]. Our study, directly researching the etiological agent, confirmed a low circulation of the disease among the wild boar population in the Emilia-Romagna region, as reported in other Italian regions [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…seroprevalence varies widely in different European countries; B. suis is mainly present in wild boars and in European brown hares (Lepus europaeus) [60][61][62][63][64]. A global comprehensive literature review and meta-analysis of Brucella in pigs from 2000 to 2020 reported that the overall prevalence of brucellosis in wild boars between 2006 and 2010 was 22.3%, while after 2010, the prevalence gradually decreased after the WOAH proposed control safety standards for animal production [65]. Our study, directly researching the etiological agent, confirmed a low circulation of the disease among the wild boar population in the Emilia-Romagna region, as reported in other Italian regions [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…However, wild boars and domestic pigs continue to be the primary source of infection for ruminants residing in the same areas. Furthermore, the presence of small ruminants and wild animals near humans enhances the danger of disease transmission [ 10 ]. Concerning ruminants, while there is a suggestion that wild ruminants might carry brucellosis and potentially transmit it to domestic animals or humans, the prevailing belief is that these wild animals are more likely to be unintentional hosts of Brucella spp., acquiring the infection from infected livestock, rather than serving as a genuine reservoir of the disease for domestic animals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wild boars ( Sus scrofa ), domestic pigs, and various wildlife species have been identified as reservoirs of B. suis and B. abortus for both livestock and wildlife [ 8 , 9 ]. These species serve as natural hosts for B. suis biovar 2, which raises the possibility of zoonotic transmission to humans, other domestic animals, and domestic pigs, and can result in undiagnosed infections [ 10 ]. Wild boars are natural hosts for B. suis biovar 2, in which the infection passes inapparently, increasing the pathogen transmission risk to domestic pigs, other domestic animals, and humans [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of brucellosis is generally achieved either directly or indirectly via Brucella isolation or the detection of specific antibodies [ 50 ]. Nevertheless the most reliable method and a gold standard of diagnosis of Brucella is isolation and, then, identification of the bacteria [ 51 ]; its performance is, however, not only time-consuming and difficult but also poses a great infection risk to workers in the laboratory, thus, necessitating specific biosafety procedures.…”
Section: Introductionmentioning
confidence: 99%